Murder, Inc. : the CIA under John F. Kennedy - Johnston, James H., 1944- ([Lincoln, Nebraska] : Potomac Books, an imprint of the University of Nebraska Press, 2019)
"A chronological narrative of the CIA's assassination operations during the Kennedy Administration"--
Castro, Oswald, and Kennedy -- The Bay of Pigs -- Mongoose -- Missile crisis -- The brigade -- Fidel and Hidell -- Oswald in New Orleans -- Assassins and spies -- AMLASH -- Mexico City -- Hubris -- Carpe diem -- The plot accelerates -- The last weekend -- A barrier once removed -- John Kennedy and the rogue elephant -- Washington, Paris, and Dallas -- November 22, 1963, in Dallas -- November 22, 1963, in other cities -- The days after -- An investigation hobbled from the start -- The investigation sputters on -- Regime change -- The Warren Report -- The never ending investigations -- John Kennedy and the CIA -- Lyndon Johnson and the CIA -- Appendix A. Where it might have led -- Appendix B. Richard Helms testimony on the assassination investigation -- Appendix C. Sources and secret files.
Includes bibliographical references and index.
Online resource; title from digital title page (EBSCOhost, viewed on March 2, 2021).
JSTOR
Keywords: United States. -- Central Intelligence Agency -- History -- 20th century; United States. -- Central Intelligence Agency -- Corrupt practices; Kennedy, John F. -- 1917-1963.; Kennedy, John F. -- 1917-1963.; Kennedy, John F. -- 1917-1963; United States. -- Central Intelligence Agency; Intelligence service -- United States -- History -- 20th century; Assassination -- United States -- History; United States -- Foreign relations -- 1961-1963.; Assassinat -- États-Unis -- Histoire; États-Unis -- Relations extérieures -- 1961-1963.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; HISTORY -- United States -- 20th Century; Assassination; Corruption; Diplomatic relations; Intelligence service; United States; 1900-1999; History